The Evolving Field of Stereotactic Body Radiation Therapy in Pancreatic Cancer - Maged Ghaly, MD; Emile Gogineni, DO; Muhammad W. Saif, MD (Pancreas, 2019)
Pancreatic cancer remains a devastating disease with dismal outcomes despite the development of novel chemotherapeutic regi mens and radiation techniques. Stereotactic body radiation therapy (SBRT) offers an advantage both in image guidance and radiation dose delivery to direct ablative doses to tumors with acceptable toxicity compared to conventional techniques. Recent literature is clustered with data pertaining to SBRT in patients with resectable, borderline resectable and locally advanced pancre atic tumors. We here present a summary of the current data and highlight the limitations and potential for future growth. Further clinical study in the form of multi-institutional trials is warranted to establish the role of SBRT in combination with new chemo therapeutic agents as well as a non-invasive alternative to surgery